Effect of some chemical and physical elicitors on some secondary compound induction of Ricinus communis through callus induction - baan munim twaij; alaa jabbar taha (Al-Mustansiriyah Journal of Science)
The results of the present study showed that AgNo3 and ABA has a negative effect on fresh and dry weight, where both of   weight significantly decreased when treated with ABA and AgNo3 compare to control treatment,  except callus treated with AgNo3 at 4mg/l, the rate of fresh and dry weight  significantly increased reached to 434,77mg respectively compared to control. Physical  treatment also had a significant effect on fresh and dry weight for callus, the highest fresh and dry weight significantly reached to 491,93 mg respectively when callus exposure  for 10 minutes to UV ray. The exposure to light for different period had negative effect on the rates of fresh and dry weight, as the control superior significantly for all lighting treatment. The concentration of all the secondary compounds extracted from callus increased significantly compared to their concentration in the seed extract. The addition of chemical treatments to callus lead to the difference in the concentration of secondary compounds. The quercetin compound reached its highest and significantly to 95.17μg/ml at the concentration of 4mg/l of AgNo3. while kaempferol suffer significantly decrease at all concentration of AgNo3, and reached to highest value significantly at control 114.76μg/ml, added concentration at 6 mg/l of AgNo3 had a positive effect in increasing the concentration of Ricinin significantly to 119.90μg/ml.  Show the results of Callus treatment with ABA, different in the concentration of secondary compounds compared with control, where control treatment significantly increase kaempferol and qurecetin compound, were reaching to71.41,114.76μg/ml respectively. While the concentration of ricinin significantly increased to 194.34μg/ml at 2mg/l ABA concentration compared to control. The physical treatment had a significant effect on the concentration of secondary compounds, the concentration of all compounds was highest significantly when callus exposure for 24 hour to light compared to control. There was no significant effect on the concentration of secondary compounds at callus exposure to UV for tow period of exposure